Decreased plasma glutamine level and CD4+ T cell number in response to 8 wk of anaerobic training - Hack, Volker; Weiss, Claus; Friedmann-Bette, Birgit; Suttner, Stefan; Schykowski, Michael; Erbe, Natalie; Benner, Axel; Bärtsch, Peter; Dröge, Wulf (American journal of physiology. Endocrinology and metabolism, 1997)
The purpose of the present study was to investigate the role of plasma amino acids and glutathione (GSH) on the absolute number of leukocyte and lymphocyte subpopulations in response to different training programs. Healthy untrained subjects were randomly assigned to an 8-wk aerobic (AET) or anaerobic (ANT) exercise training program. Absolute number of cell counts did not significantly change in AET, whereas a decrease of CD4+ T cell counts (P < 0.05), a fall in cells expressing CD45RA+ antigen (P < 0.05), and a marked increase in CD8+ T cell numbers (P < 0.01) were noted in ANT at the end of the training period compared with baseline values. Furthermore, ANT demonstrated a marked rise (P < 0.001) in plasma glutamate from 27.6 +/- 2.8 to 49.8 +/- 5.2 microM and a considerable reduction (P < 0.001) of the plasma glutamine pool from 713 +/- 22 to 601 +/- 30 microM after 8 wk of training. The decrease in glutamine showed a strong positive correlation to the individual loss of CD4+ T cells (r = 0.67, P < 0.001). AET demonstrated a rise (P < 0.05) in GSH from 20.7 +/- 2.5 to 28.1 +/- 1.5 nmol/mg protein at terminal examination. In conclusion, our data indicate impairment of the number and activity of CD4+ T cells in response to 8 wk of ANT, which might be linked to metabolic factors such as glutamine.